Practice in industry training in fish processing technology. - De Los Reyes, Erminia M. (College of Fisheries, University of the Philippines in the Visayas, 1978)
The spoilage of fish is retarded when its temperature is lowered thereby creating an environment unfavorable for bacteria to grow. Once the fish is frozen it should stay that way until sold. To obtain a good quality frozen fish one must use the best quality fresh fish. Freezing can preserve the quality of the fish before it was frozen, and since it is a perishable product, it should be frozen as soon as it leaves the water. There are several methods of freezing such as brine contact freezing, indirect contact freezing, sharp freezing and air blast freezing.